Donor‐Stabilized Silylene/Phosphine‐Supported Carbon(0) Center with High Electron Density. (5th May 2017) - Troadec, Thibault; Wasano, Tatsuya; Lenk, Romaric; Baceiredo, Antoine; Saffon‐Merceron, Nathalie; Hashizume, Daisuke; Saito, Yosuke; Nakata, Norio; Branchadell, Vicenç; Kato, Tsuyoshi
Abstract: An isolable donor‐stabilized silavinylidene phosphorane was synthesized. This molecule, which can also be regarded as a new carbon(0) complex featuring a phosphine and a donor‐stabilized silylene ligand, presents a central carbon atom with a remarkably high electron density (−1.82). Furthermore, the experimental electron‐density study of this compound demonstrates the delocalization of the σ‐lone pair at the central carbon atom toward the silicon center, a feature which is remarkably different from electronic situation of other bent‐allene‐type molecules. This result clearly demonstrates the powerful electron‐donating ability of donor‐stabilized silylene ligands, as well as their excellent electron‐acceptor properties.